Factors associated with early sexual intercourse among teenagers and young adults in rural south of Benin - Yolaine Glèlè Ahanhanzo; Charles Sossa-Jérôme; Ghislain Sopoh; Makilioubè Tchandana; Colette Azandjèmè; Toyi Tchamdja (AOSIS, 2018)
Early initiation to sexual intercourse increases the risk of sexually transmitted infections including HIV/AIDS and early or unwanted pregnancies. This study aimed identifying the factors associated with the early initiation to sexual intercourse among teenagers and young adults aged 10-24, in the south of Benin. A cross-sectional study was conducted in the south of Benin where 360 respondents were selected by random cluster sampling. Multiple logistic regressions was used to find related factors to early sexual intercourse. The significance level for the tests was of 5%. The average reported age of initiation to sexual intercourse was 14.75±2.18. Among the male teenagers and young adults, 41.11% had an early sexual intercourse against 20.24% for the female gender (P<10-3). The lack of communication between parents-teenagers (P=0.003), level of education of the father (P=0.021), exposure to pornographic movies (P=0.025), an adverse opinion on premarital sexual abstinence (P=0.026) were significantly associated with early sexual intercourse. Communication about health promotion for behavioural change may contribute to delay the age of sexual initiation.